Analytics for business and management students: essential in gaining meaningful employment? - Tegwen Malik (The Chartered Association of Business Schools (CABS) Learning, Teaching and Student Experience (LTSE) Conference 2023, ICC Wales, May 22-23 2023, 2023)
Analytics can be considered a complex yet necessary area of demand within the business world. This discussion will provide a platform for practitioners who deliver analytic modules for business to consider the benefits students can gain from attending such modules. The delivery approaches (and experiences) of academics will be explored along with consideration given to positive student outcomes and employability skills in this specialised field.